2017
DOI: 10.1080/10410236.2017.1351852
|View full text |Cite
|
Sign up to set email alerts
|

Communicated Sense-making After Miscarriage: A Dyadic Analysis of Spousal Communicated Perspective-Taking, Well-being, and Parenting Role Salience

Abstract: Grounded in communicated sense-making (CSM) theorizing, we investigated communicated perspective-taking (CPT; i.e., conversational partners' attendance to and confirmation of each other's views) in association with individual and relational well-being in married couples who had miscarried (n = 183; N = 366). Actor-partner interdependence modeling revealed husbands' perceptions of wives' CPT were positively related to husbands' positive affect about the miscarriage and both spouses' relational satisfaction, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
1
25
2
Order By: Relevance
“…Compared to other types of bereavement, individuals coping with miscarriage tend to receive less emotional support from family and friends because miscarriage is not generally talked about (Bute & Brann, 2015). As a result, partners often turn to each other for support, such that they may collectively seek to make sense of their loss (Frost et al, 2007; Horstman & Holman, 2018). At the same time, some women report that miscarriage causes tension in their marital relationship (McGreal et al, 1997).…”
mentioning
confidence: 99%
“…Compared to other types of bereavement, individuals coping with miscarriage tend to receive less emotional support from family and friends because miscarriage is not generally talked about (Bute & Brann, 2015). As a result, partners often turn to each other for support, such that they may collectively seek to make sense of their loss (Frost et al, 2007; Horstman & Holman, 2018). At the same time, some women report that miscarriage causes tension in their marital relationship (McGreal et al, 1997).…”
mentioning
confidence: 99%
“…Storylistening can also be challenging because bearing witness to others' stories of difficulty or trauma can be a burden to the listener (Shortt & Pennebaker, 1992), resulting in emotional contagion (Miller, Stiff, & Ellis, 1988), emotional exhaustion (Boyas, Wind, & Kang, 2012), and/or compassion fatigue (Figley, 2002), all of which can lead to higher levels of distress. Storylisteners who engage in high levels of communicated perspective-taking may also experience negative outcomes, such as decreased positive affect (for women specifically; Horstman & Holman, 2017) or decreased relational satisfaction (Vorauer & Sucharyna, 2013). Despite these challenges, stress, illness, and relational problems call for storytelling (Frank, 1995).…”
Section: The Challenges Of Narratively Making Sense Of Difficultymentioning
confidence: 99%
“…Research has identified links between CPT and family functioning, perceptions of family supportiveness (Trees & Koenig Kellas, 2009), the positivity of one's own narrative framing (Horstman et al, 2016), and husbands' mental health (Koenig Kellas et al, 2010). This research informed the creation of an other-report survey measure of CPT (OCPT) which has been used to assess friends' perceptions of each other during storytelling interactions (Koenig Kellas et al, 2015) and spouse's marital satisfaction and affect in the context of miscarriage (Horstman & Holman, 2017). Finally, The Communicated Perspective-Taking Rating System (CPTRS, Koenig Kellas et al, 2017) was developed for observational rating of CPT behaviors including attentiveness, agreement, affective tone, validating identity, creating space to talk, and global ratings of CPT attentiveness and confirmation.…”
Section: Cptmentioning
confidence: 99%